Development and Survival of Lygus hesperus (Hemiptera: Miridae) Nymphs Under Constant and Variable Temperatures. Issue 1 (11th February 2019) - Spurgeon, Dale W; Brent, Colin S
Abstract: Thermal environments of the arid western United States are often harsh compared with the ranges of temperatures favorable for development and survival of crop insect pests. In cotton [ Gossypium spp. (Malvales: Malvaceae)], new irrigation practices such as deficit irrigation may impact populations of pest and beneficial arthropods by temporarily altering temperature profiles within the plant canopy. Most information regarding the temperature-dependent development and survival of an important cotton pest, the western tarnished plant bug ( Lygus hesperus Knight), is derived from constant temperature studies. We examined the development and survival of L. hesperus nymphs under constant (±0.2°C) and variable (±8°C) temperature regimes at daily mean temperatures of 15, 22, and 29°C. Under the low temperature (15°C), stadium lengths and duration of the nymphal stage were shorter when temperatures were variable compared with a constant temperature. No differences in development times were observed between regimes at the medium temperature (22°C). Except for the first stadium, development times under the high variable temperature regime were longer compared with the high constant regime (29°C). Nymph survival was unaffected by temperature regime except at the lowest temperature, where daily thermal fluctuations substantially improved survival compared with the constant conditions. These results suggest that temporarily increased crop canopy temperatures caused by altered irrigation schemes are unlikely to substantially reduce the growth of L. hesperus populations. However, enhanced nymphal development and survival under low variable temperatures likely contribute to the survival of overwintering L. hesperus in the absence of acute, low-temperature mortality.